Teaching faculty perceptions, attitudes, challenges, and satisfaction of online teaching during COVID-19 pandemic in Saudi Arabia: A national survey - Alqahtani, Jaber S.; Aldhahir, Abdulelah M.; Al Ghamdi, Shouq S.; Aldakhil, Ahmad M.; Al-Otaibi, Hajed M.; AlRabeeah, Saad M.; Alzahrani, Eman M.; Elsafi, Salah H.; Alqahtani, Abdullah S.; Al-maqati, Thekra N.; Alnasser, Musallam; Alnaam, Yaser A.; et al. (Frontiers in Education, 2022)
Background: The COVID-19 pandemic and associated preventative measures introduced a shock to the teaching paradigm in Saudi Arabia and the world. While many studies have documented the challenges and perceptions of students during the COVID-19 pandemic, less attention has been given to higher education staff. The aim of the present investigation is to evaluate the staff’s perception and experiences of online teaching during the COVID-19 pandemic. Method: A validated survey was conducted between December 2021 and June 2022 in Saudi Arabian Universities to assess the status of online teaching during the COVID-19 pandemic among faculty members. The collected responses were exploratively and statistically analysed. Results: A total of 1117 response was received. About 66% of the respondents were male and 90% of them hold postgraduate degree. Although rarely or occasionally teach online pre-COVID-19, only 33% of the respondents think the transition was difficult and 55% of them support the move. Most respondents received adequate training (68%) and tools (80%) and 88% of the respondents mentioned that they did not accrue additional workload in online study design. While the perception of online teaching was mostly positive (62%) with high satisfaction (71%). However, 25% of the respondents reported that a poor internet bandwidth was an obstacle and 20% was unable to track students’ engagement. Respondents with more years of experience, previous training, support, or perceived online transition as easy were also more likely to be satisfied with the process. Also, older respondents, those who support the transition and those with previous training were less likely to report barriers (all p<0.001). Conclusion: The perception and experience of transition to online teaching during the COVID-19 pandemic in Saudi Arabia were positive. Low internet bandwidth and inability to track students’ limited effective online teaching. Work experience, previous training, and positive perception are the main factors that influence staff online teaching satisfaction.